An Overview of Work Contentment: A Social Analysis of Lebanese and US Workers - Ali, Halawi; Wael, Zaraket (European Scientific Journal, ESJ, 2017)
This paper studies and investigates workers in USA and Lebanon, their observed mood of work satisfaction as well as their occupation in both service and manufacturing businesses. The outcomes demonstrate unanticipated divergences and resemblances in the workers’ replies. Hypotheses, founded on Hofstede’s Individualism (IDV), foresees that national variances in Lebanon and USA would lead to a greater insight into work contentment of workers in USA vs. their counterparts in Lebanon.